The Impact of Brand Attitude on Brand Image and Equity in The Indonesian Outdoor Industry - Atmaja, Dodi Ria; Atsir, Achmad Zaidan (Majalah Ilmiah Bijak, 2024)
This study examines the impact of brand attitude on brand image and brand equity for the Eiger Indonesia brand. In the context of intense competition in the outdoor products industry, understanding the influence of consumer attitudes on brand image and equity is crucial for effective marketing strategies. This study aims to analyze the relationship between brand attitude, brand image, and brand equity in the context of Eiger Indonesia. The research population is social media users who buy products from Eiger Indonesia. This research uses a quantitative approach with a survey method involving 160 consumers of Eiger products. Data collection used purposive sampling method through online questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that a positive attitude towards the brand significantly improved brand image, and a strong brand image contributed significantly to brand equity. Eiger is advised to explore more focused marketing strategies based on the findings of this study, to strengthen consumers' positive attitudes and brand image, and maximize their brand equity. The implications of this study significantly contribute to Eiger's brand equity showing that a positive brand image not only strengthens brand perception, but also increases brand value in the eyes of consumers.